One Lung Ventilation and Erector Spinae Plane Block in a Child with Posterior Mediastinal Tumour: A Case Report - Neeta Verma; Prachi Siddharth Kamble (JOURNAL OF CLINICAL AND DIAGNOSTIC RESEARCH, 2026)
Tumours located in the posterior mediastinum of children present unique anaesthetic challenges because they are in proximity to large vessels and the airway, which puts the child at risk for airway compression, difficulty breathing, and loss of haemodynamic stability during surgery. This case describes the perioperative anaesthetic management of this eight-year-old girl, weighing 23 kg, with a large ganglioneuroma that extended from D1 to D7 in the posterior mediastinum. Because of the risk of airway compromise, an Awake Fibreoptic Intubation (AFOI) was performed while allowing the child to breathe on her own before General Anaesthesia (GA) was induced. To achieve lung isolation and enable One-Lung Ventilation (OLV), a 5 Fr paediatric bronchial blocker was used under fibreoptic guidance. During OLV, lung-protective ventilatory strategies were used, and oxygenation and haemodynamic stability were maintained throughout. Postoperatively, she received analgesia with an Erector Spinae Plane Block (ESPB) using 0.25% bupivacaine under ultrasound guidance. Her intraoperative and postoperative courses were uncomplicated. This case stresses the need for careful preoperative assessments, maintenance of spontaneous ventilation until airway control has been established, appropriate techniques for lung isolation, and multimodal analgesic therapy for safe anaesthetic management of posterior mediastinal tumours in children.